Investigation of bulk magneto-resistance crossovers in iron doped zinc-oxide using spectroscopic techniques - Ali, Liaqat; Shah, Wiqar H.; Ali, Akhtar; Eldin, Sayed M.; Al-Jaafary, Abdullah A.; Sedky, A.; Mazher, Javed; Imran, Naveed; Sohail, Muhammad (Frontiers in Materials, 2023)
Pellets of Pure and Fe-doped dilute magnetic semiconducting (DMS) samples are studied for bulk magneto-resistance (BMR) at room temperature and at low-temperatures ~100K. Raman-, photoluminescence- and X-ray photoelectron-spectroscopic techniques are used to determine chemical and electronic structures of the samples. A broadband intense yellow-green-orange luminescence is observed in Fe-doped ZnO samples and emission red-shifts are investigated. Electrical transport is studied with and without applied magnetic field up to 9T and thermal activation and hopping modes of conduction is discussed in light of nature of Fe substitution in the host lattice. Several decremental- to incremental-BMR crossovers are obtained corresponding to experimental variables of Fe concentration 0.025≤ x≤0.1, temperature and applied magnetic field. Several possible modes of magneto-transport are discussed to further elucidate the origin of the as-found BMR crossovers in our samples. Positive BMR in pure- and highly doped (x≥0.1) ZnO is found to originate from F-centers and thermal fluctuations, respectively. However, modestly doped (x≤ 0.05) ZnO exhibit thermally activated conduction and magnetic poloron mediated negative BMR.